IMPLEMENTATION OF HUFFMAN AND LZ78 ALGORITHM FOR CHARACTER COMPRESSION - Chairul Imam; Muhammad Furqon Siregar (Sean Institute, 2022)
The Huffman algorithm is a time complexity of 0(n log n), because the Huffman algorithm performs one iteration process when merging two trees that have the smallest frequency at a root takes 0(log n), and the process is done many times until only there is only one tree left with a combination of the LZ78 algorithm using a dictionary technique in compressing one of the characters in the form of a string replaced by a table code that is made for reference in extended ASCII in inputting characters or strings.